Data protection and migration: balancing state interests and individual rights - Martens, Ruzayda (My University, 2015)
The globalization of irregular migration and its facilitation by transnational criminal groups, coupled with concerns of terrorism, has radically impacted the way in which States manage migration and national security. At the same time, the information age has placed the issue of privacy and confidentiality at the centre of public, legislative and media debates. While advanced technology facilitates migration management and data exchange, the emergent use of surveillance techniques to identify individuals and keep track of their movements is a growing concern. Advanced technology can help to protect and manage borders, but it can also threaten human rights and create vulnerabilities relating to data theft, data loss, inappropriate disclosure and misuse of personal data. In the absence of appropriate data protection safeguards, personal data can be used for reasons unrelated to its intended purpose, without the knowledge of the individuals concerned and contrary to their expectations. When applied to migrants, data protection has a cross-border dimension, and this gives rise to additional concerns related to unauthorized disclosure that could lead to a multitude of risks ranging from physical violence to profiling and discrimination. This thesis seeks to outline the points of intersection between data protection and migration. In so doing, it points out the important consideration of the threat to human life and safety, a practical reality when collecting and processing personal data of vulnerable migrants. States have an obligation to protect the human rights afforded to all individuals, regardless of their nationality or immigration status. States also have the sovereign right to protect their borders and the duty to keep their citizens secure. While acknowledging the delicate exercise of having to balance between protecting State interests and respecting individual rights, this thesis emphasizes that the two are not mutually exclusive and it can be balanced, albeit a delicate balance. To ensure an appropriate balance, individual rights should not be diluted or subjugated by the interests of States. Instead any restrictions to privacy and data protection should be justified and proportional to the state interest. Further, the parameters for using advanced technology should be firmly embedded in the law. Finally, as technology is not infallible and cannot be seen in isolation, the human factor is a key consideration to take into account when developing and implementing the law governing the use of advanced technology that may impact on individual rights.
Thesis (L.L.M. (Dissertation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2014.